Investigating Physiotherapists’ Knowledge, Attitude, and Practice of Evidence-Based Practice in Indonesia - Bachtiar, Farahdina; Condrowati, Condrowati; Purnamadyawati, Purnamadyawati; Rabia, Rabia (Faculty of Nursing, Universitas Hasanuddin, 2023)
Introduction: In order to deliver quality care to patients and clients, physiotherapists should implement Evidence Based Practice (EBP) in the area of clinical services. There has been little research into the adoption of EBP among physiotherapists in Indonesia. Aims: This study aims to investigate the attitudes, knowledge, and practice of physiotherapists in Indonesia regarding EBP. Methods: A descriptive, cross-sectional research approach was used to assess physiotherapists' attitudes, knowledge, and practice in Indonesia. An online self-administered questionnaire-based survey containing validated Indonesian versions of the Evidence Based Practice Questionnaire (EBPQ) and sociodemographic variables was distributed to physiotherapists via social media. Results: The questionnaire was completed by 156 physiotherapists, with 73 (46.8 %) men and 83 (53.35 %) women participating. The total EBP Questionnaire (EBPQ) average score was 127.67, with a mean of 5.31 out of 7 (SD = 0.96). The attitude (5.23, S D= 0.95) had the highest EBP score, followed by knowledge (5.25, SD=1.01) and practice (5.23, SD=1.30). Education level (p = 0.001), professional category (p = 0.002), and clinical instructor (p = 0.024) were the characteristics related with increased EBP performance. Conclusion: In summary, physiotherapists in Indonesia have positive attitudes, knowledge, and practices towards EBP. Higher education levels, working as a clinician and educator, and teaching clinical students may all help to enhance EBP implementation.